Insights into amphicarpy from the compact genome of the legume Amphicarpaea edgeworthii. Issue 5 (11th December 2020) - Liu, Yiyang; Zhang, Xuejie; Han, Kai; Li, Rongchong; Xu, Guoxin; Han, Yan; Cui, Feng; Fan, Shoujin; Seim, Inge; Fan, Guangyi; Li, Guowei; Wan, Shubo
Abstract: Amphicarpy (seed heteromorphy) is a unique and fascinating reproductive strategy wherein a single plant produces both aerial and subterranean fruits. This strategy is believed to be an adaptation to life under stressful or uncertain environments. Here, we sequenced and de novo assembled a chromosome‐level genome assembly of the legume Amphicarpaea edgeworthii Benth. The 299‐Mb A. edgeworthii genome encodes 27 899 protein‐coding genes and is the most compact sequenced legume genome reported until date. Its reduced genome size may be attributed to the reduced long‐terminal repeat retrotransposon content, which stems from the unequal homologous recombination. Gene families related to immunity and stress resistance have been contracted in A. edgeworthii, which is consistent with the notion that the amphicarpic reproductive strategy may be a complementary mechanism for its weak environmental‐adaptation ability. We demonstrated the 'ABCE' model for the differentiation of chasmogamous and cleistogamous flowers. In addition, the characteristics of aerial and subterranean seeds in hard‐seededness were explored. Thus, we suggest that the A. edgeworthii genome, which is the first of an amphicarpic plant, offers significant insights into its unusual reproductive strategy that is a key resource towards comprehending the evolution of angiosperms.